(3JgPjH GddZIs - (3eMeO Hf CMeO Hf GdCRgQj GdgQhj, CHh efUhQ,J (B370 (3g` s ((3Ydi Hf eMeO Hf UObI Hf TjH GdNaGLi GdMfai s)
(3ChdgG (B:s
(3MQa GdSjf CHhGH GdeVGYa S W KYdH Yf GHf GdCYQGHi GdCSW ef GdQLGd GdWhjd GdQLdjf s
(3BNQgG (B:s
(3BNQ cJGH GdWGA jJdhg ai Chd GdMGOi YTQ cJGH GdOGd CHhGH GdeVGYa s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B311 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B230s
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
Keywords: (3GddZIs